IMPROVING ACCESS TO ACTIVITIES IN A GROUP CARE SETTING BY ADDRESSING AGE-RELATED HEARING LOSS - Mamo, S. (Innov Aging, 2017)
Untreated age-related hearing loss can exacerbate dementia-related problem behaviors and interfere with a person’s ability to listen, follow instructions, and communicate, especially in a group care setting. The intervention presented in this session aims to improve access to activity participation by improving the listening environment, providing staff training in communication strategies, and using over-the-counter amplification on an individual basis to support adults with both hearing and cognitive impairments. After addressing the physical and social context (i.e., room acoustics and staff training), target individuals were offered an amplification device during activities and meals in a group care setting. The primary outcomes focused on participation, engagement, and communication behaviors that were directly observed in the activity hall. This approach to addressing hearing loss in the group care setting allows for on-site staff to support improved communication and in turn, enhance activity participation among at risk individuals.